Measuring the effect of competitive teacher recruitment on student achievement: Evidence from Ecuador - Maria Daniela Araujo P. (Bamberg University, Bamberg Economic Research Group (BERG), 2019)
In the last decade, several Latin American governments have implemented new teacher recruitment policies based on evaluations of candidates' competency and knowledge so as to raise the quality of their teachers and schools. Since 2007, the Ecuadorian government has required teacher candidates to pass national standardized tests before they can participate in merit-based selection competitions for tenure at public schools. Has this new recruitment system served as an effective screening device? Has it ultimately helped to raise student learning? To answer these questions, I analyze data from a unique Ecuadorian survey of schools in the academic year 2011-2012. I first estimate the value-added to student achievement using OLS and hierarchical linear regressions to evaluate the effect of Ecuador's new competitive recruitment policy. I then use propensity score matching to simulate a random assignment of students to teachers and estimate causal treatment effects. The evidence suggests that teachers who were granted tenure through the new competitive recruitment policy were no more effective, overall, in raising students' learning in reading or math than their peers at schools. Nonetheless, poorer children who were assigned to these teachers had significantly better scores in reading. Furthermore, test-screened teachers, regardless of their tenure status, seem to have had positive significant effects in reading, particularly for students living in poverty. This finding suggests that Ecuador's teacher recruitment policy had a positive impact on the nation's most vulnerable students.
Keywords: I20; I21; I28; J45; 330; teacher quality; education policy; education reform; Latin America